Growth rate of capon and female pigs without service under the same diet housed by sex difference (Semiárida, 2020)
Daily weight gains of barrow and gilts from 40 to 100 Kg live weight, were compared under a similar feeding treatment. Three groups of eight pigs each were allocated in two boxes. Forty-eight crossed and backcrossed Duroc Jersey x Hampshire pigs were used. Barrows showed significant greater daily gains in relation to the mixed group (0,948, 0,867 and 0,852 Kg/day respective ly). When gilts and mixed groups were compared, gilts showed a better performance but differences were not significant (P:0,05). Greater differences of daily gain of barrows were obtained during the finishing period (1,000,0,869 and 0,849 Kg/day respectively). Sailing prices at the Mercado Nacional de Haciendas showed no differences between groups.
Keywords: pigs